Sağlık Bilimleri Fakültesi Öğrencilerinin Sağlık Okuryazarlığı Düzeylerinin İncelenmesi / Examining the Health Literacy Levels of Health Sciences Faculty Students - Yılmaz Güven, Durdane; Bulut, Hülya; Öztürk, Sercan (Journal of History Culture and Art Research, 2018)
Abstract This study aims to examine the health literacy levels of health sciences faculty students. This descriptive and cross-sectional study was carried out between April 07 and June 1, 2017, with the students of Karabük University Health Sciences Faculty, who accepted to participate in the study (n = 300). The research data was collected using a survey form questioning participants’ socio-demographic characteristics, and the "Turkish Health Literacy Scale 32 (THLS-32)". The chi-square, Mann Whitney U and Kruskal Wallis H tests were used for statistical evaluation. The Bonferroni correction was used in the post hoc evaluation of the differences found as a result of the Kruskal Wallis H test. The mean age of the participant students was 20,89 ± 1,74 years. Of the 85,3% (n=256) of them were female and 14,7% (n=44) were male. In addition 33,3% (n=100), 26,3% (n=79), 22,3% (n=67) and 18% (n=54) of the students were studying in nursing, midwifery, child development, and physiotherapy & rehabilitation faculties. The 55,7% of the students obtained a score corresponding to an "adequate or excellent health literacy" level on the whole scale, 62% in subscale of "treatment and service", and 55% in subscale of "protecting from diseases and improving health". It was determined that the students had the highest and lowest mean scores on the subscales of "using/applying health-related information" and "evaluating health-related information", respectively. Moreover, it was found that the students in midwifery and physiotherapy & rehabilitation faculties obtained the highest (36,24 ± 6,16) and lowest (31,26 ± 6,32) total scores on the THLS-32 scale, respectively (p <0.001). The study results suggest that students studying in health education do not have the desired level of health literacy. Health professionals who will serve as health educators and counsellors in their professional fields should have good levels of health literacy for fulfilling their roles in this regard. Therefore, it is recommended to add the subject of health literacy to pre-graduation health curriculum and course schedule in universities. Öz Bu çalışma Sağlık Bilimleri Fakültesi öğrencilerinin sağlık okuryazarlığı düzeylerinin incelenmesi amacıyla yapılmıştır. Çalışma tanımlayıcı ve kesitsel tiptedir. Çalışma Karabük Üniversitesi Sağlık Bilimleri Fakültesi’nde 07.04 - 01.06.2017 tarihleri arasında, araştırmayı kabul eden öğrencilerle (n=300) yapılmıştır. Verilerin toplanmasında sosyo-demografik özelliklerinin sorgulandığı anket formu ve “Türkiye Sağlık Okuryazarlığı Ölçeği-32 (TSOY-32)” kullanılmıştır. İstatistiksel değerlendirmede ki-kare testi, Mann Whitney U testi ve Kruskal Wallis H testinden yararlanılmıştır. Kruskal Wallis H testinde çıkan farklılıkların post hoc değerlendirmesinde Bonferroni düzeltmesi kullanılmıştır. Öğrencilerin yaş ortalaması 20,89±1,74 yıl olup, %85,3’ü (n=256) kadın, %14,7’sı (n=44) erkektir. Öğrencilerin % 33,3’ü (n=100), hemşirelik, %26,3’ü (n=79) ebelik, %22,3’ü (n=67) çocuk gelişimi, % 18,0’ı (n=54) fizyoterapi ve rehabilitasyon bölümünde eğitim görmektedir. Ölçek puanlarına göre öğrencilerin “yeterli ya da mükemmel sağlık okuryazarlığı” düzeyine sahip olma oranı, ölçek toplamında %55,7, “tedavi ve hizmet” alt boyutunda %62,0, “hastalıklardan korunma ve sağlığın geliştirilmesi” alt boyutunda %55,0’dır. Öğrencilerin “sağlıkla ilgili bilgiyi kullanma/uygulama” boyutunda en yüksek puanlara sahip olduğu, en düşük puanların ise “Sağlıkla ilgili bilgiyi değerlendirme” boyutunda olduğu belirlenmiştir. TSOY-32 ölçeği toplam puanları, bölümlere göre değerlendirildiğinde, en yüksek puanı ebelik bölümü öğrencilerinin (36,24±6,16) aldığı, fizyoterapi ve rehabilitasyon bölümü öğrencilerinin ise (31,26±6,32) en düşük puana sahip olduğu saptanmıştır (p<0,001). Çalışmanın sonuçları sağlık alanında eğitim gören öğrencilerin istenilen sağlık okuryazarlığı düzeyine sahip olmadığını göstermektedir. Mesleki alanlarıyla ilgili sağlık eğitimcisi ve danışmanı olarak görev yapacak olan sağlık çalışanlarının, bu rollerini yerine getirebilmeleri için sağlık okuryazarlığı düzeylerinin iyi olması gerekir. Bu nedenle mezuniyet öncesi müfredat ve ders programları içinde sağlık okuryazarlığı konusunun yer alması önerilmektedir.